The Injectable Contraceptive Medroxyprogesterone Acetate Attenuates Mycobacterium tuberculosis–Specific Host Immunity Through the Glucocorticoid Receptor. (19th November 2018) - Tomasicchio, Michele; Davids, Malika; Pooran, Anil; Theron, Grant; Smith, Liezel; Semple, Lynn; Meldau, Richard; Hapgood, Janet Patricia; Dheda, Keertan
Abstract: Background: The effects of the widely used progestin-only injectable contraceptives, medroxyprogesterone acetate (MPA) and norethisterone acetate (NET-A), on host susceptibility to Mycobacterium tuberculosis ( Mtb ) are unknown. Methods: We recruited human immunodeficiency virus–uninfected females, not taking any contraceptives, from Cape Town, South Africa, to evaluate the effect of MPA, NET-A, and dexamethasone on Mtb containment in monocyte-derived macrophages co-incubated with purified protein derivative (PPD)–driven peripheral blood–derived effector cells. Results: MPA ( P < .005) and dexamethasone ( P < .01), but not NET-A, significantly attenuated Mtb containment in Mtb -infected macrophages co-cultured with PPD-driven effector cells at physiologically relevant concentrations and in a dose-dependent manner. Antagonizing the glucocorticoid receptor with mifepristone (RU486) abrogated the reduction in Mtb containment. In PPD-stimulated peripheral blood mononuclear cells, MPA and dexamethasone, but not NET-A, upregulated (median [interquartile range]) regulatory T cells (5.3% [3.1%–18.2%]; P < .05), reduced CD4 + T-cell interferon-γ (21% [0.5%–28%]; P < .05) and granzyme B production (12.6% [7%–13.5%]; P < .05), and reduced CD8 + perforin activity (2.2% [0.1%–7%]; P < .05). RU486 reversed regulatory T-cell up-regulation and the inhibitory effect on Th1 and granzyme/perforin-related pathways. Conclusions: MPA, but not NET-A, subverts mycobacterial containment in vitro and downregulates pathways associated with protective CD8 + - and CD4 + -related host immunity via the glucocorticoid receptor. These data potentially inform the selection and use of injectable contraceptives in tuberculosis-endemic countries. Abstract : Injectable contraceptive usage is high in tuberculosis (TB)–endemic countries, and their effect on TB pathogenesis in humans has not been investigated. At physiological concentrations, medroxyprogesterone acetate, but not norethisterone acetate, attenuates Mycobacterium tuberculosis containment and antagonizes pathways associated with protective host immunity through glucocorticoid receptor–mediated mechanisms.